'Black butter melting and opening underfoot': the 'peat harvest' in Irish literature and culture. Issue 4 (1st October 2020) - O'Connor, Maureen; Gearey, Benjamin
ABSTRACT: In this paper, we discuss 'turf-cutting', or the 'harvest' of peat, a centuries-long agricultural practice in Ireland. Although healthy peatlands are known to be carbon sinks, calls for the end of peat cutting are controversial in a country still largely defined by rural traditions. We consider the relationship between peat, peat cutting and identity: the 'bog' features significantly in literature and has played a central role in notions of a specifically gendered version of 'authentic' Irishness. The cutting of peat exposes and destroys cultural heritage in the form of the archaeological record, and we contrast this reality with the representation of peat cutting in the poetry of Seamus Heaney. We then focus on the fiction of Edna O'Brien, for whom the bog is precious, meaningful, culturally and aesthetically, when left in its undisturbed state, or when explored to connect to the past rather than fuel patriarchal desires.